Is Wittgenstein a foundationalist? (2011)
The idea that On Certainty reveals a third Wittgenstein has become common in the recent literature. In particular, Avrum Stroll argues that said work sets forth a new and powerful version of non-homogeneous foundationalism. The article examines that foundationalism and defends the argument that On Certainty deploys the methodology used in the Philosophical Investigations in order to point out a new form of logical impossibility. The article also shows how Stroll defends a position associated with substantialist readings of the Tractatus, and recommends an austere reading of On Certainty.